Low and high body mass index in hidradenitis suppurativa patients—different subtypes?. (10th October 2017) - Theut Riis, P.; Saunte, D.M.; Benhadou, F.; del Marmol, V.; Guillem, P.; El‐Domyati, M.; Abdel‐Wahab, H.; Antoniou, C.; Dessinioti, C.; Gürer, M.A.; Beksaç, B.; Szepietowski, J.C.; et al.
Abstract: Introduction: Overweight is a well‐established risk factor for hidradenitis suppurativa (HS). In this cross‐sectional study, we compare HS patients with a high body mass index (BMI) with HS patients with a low BMI to investigate differences in disease characteristics. Materials and method: Patients were recruited from 17 dermatological centres from four continents. A total of 246 patients with a BMI below 25 were compared to 205 patients with a BMI of above 35. Results: Patients with a high BMI suffered more severe disease (Hurley, physician global assessment, number of areas affected and patient‐reported severity (PRS), P < 0.001 for all). There was no difference in smoking ( P = 0.783) nor in family history ( P = 0.088). In both low and high BMI patients, early onset of HS was a predictor of positive family history ( P < 0.001, for each). For low BMI patients, an increase in BMI significantly increased PRS ( P < 0.001). For patients with a high BMI, number of pack‐years significantly increased PRS ( P = 0.001). Cluster analysis of eruption patterns was location specific for low BMI patients but severity specific for high BMI patients. Discussion: Patients with a low and high BMI could represent two clinically different subtypes. We suggest a non‐linear relationship between BMI and impact of HS. As patients go from a low BMI patient to a high BMI patient (or from high to low), eruption patterns and risk factors may change.